An organic electrophosphorescent material and its application
By developing a new organic electrophosphorescence luminescent material, using the hybrid coordination combination of metal atom M with specific ligands, the existing materials have been solved in terms of color purity and luminescence efficiency, and the efficient and reliable organic electrochemical system has been achieved. Electroluminescent device performance.
Patent Information
- Application Number
- CN202211096686.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-09-08
AI Technical Summary
Existing organic electroluminescent materials have shortcomings in color purity and luminescence efficiency, and have a short lifespan, making it difficult to meet the needs of efficient and reliable blue or green phosphorescent materials.
A novel organic electrophosphorescence luminescent material has been developed to form an efficient phosphorescent luminescent material for the luminescent layer of organic electroluminescent devices through the hybrid coordination of metal atom M with a specific ligand.
It realizes the superior performance of high purity, high brightness and high efficiency of organic electroluminescent devices, significantly improves color purity and luminescence efficiency, and extends the life of the device.
Smart Images

Figure CN115572315B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic electroluminescent display, and in particular to a novel organic electrophosphorescent luminescent material and its application in an organic electroluminescent device. Background Art
[0002] Electroluminescent display devices can be divided into inorganic electroluminescent display devices and organic electroluminescent display devices according to the different materials constituting the light-emitting layer. Compared with inorganic electroluminescent display devices, organic electroluminescent display devices have incomparable advantages, such as full-color luminescence in the visible spectrum, extremely high brightness, extremely low driving voltage, fast response time and simple manufacturing process.
[0003] The research on organic electroluminescence started in the 1860s. Pope first realized electroluminescence on anthracene single crystals, but the driving voltage was as high as 100V at that time and the quantum efficiency was very low. In 1987, Tang and VanSlyke used a double-layer film structure with 8-hydroxyquinoline aluminum complex (Alq3) as the light-emitting layer and electron transport layer, TAPC as the hole transport layer, and ITO electrode and Mg:Ag electrode as the anode and cathode respectively, to produce a high brightness (>1000cd / m 2 ), high-efficiency (1.5lm / W) green light organic electroluminescent thin film devices, and their driving voltage dropped below 10V. In 1990, Burroughes et al. used poly(p-phenylene phenylene) (PPV) to prepare polymer thin film electroluminescent devices to obtain a blue-green light output with a quantum efficiency of 0.05%, and its driving voltage was less than 14V. In 1991, Braun et al. used PPV derivatives to produce green and orange light output with a quantum efficiency of 1%, and its driving voltage was about 3V. These research advances immediately attracted widespread attention from scientists in various countries, and research on organic electroluminescence was widely carried out worldwide and gradually began to enter the market.
[0004] Generally speaking, the structure of an organic electroluminescent display device includes an anode formed on a substrate, and a hole transport layer, a light-emitting layer, an electron transport layer and a cathode formed on the anode in sequence. The hole transport layer, the light-emitting layer and the electron transport layer are organic thin films composed of organic compounds. The driving principle of an organic electroluminescent display device with the above structure is as follows: as long as a voltage is applied between the anode and the cathode, holes are injected from the anode through the hole transport layer into the light-emitting layer; at the same time, electrons are injected from the cathode through the electron transport layer into the light-emitting layer; in the light-emitting layer region, carriers are rearranged to form excitons, and the excited state excitons are converted to the ground state, causing the light-emitting layer molecules to emit light.
[0005] Luminescent materials are divided into two groups according to the luminescence mechanism, one group is fluorescent materials that utilize singlet excitons, and the other group is phosphorescent materials that utilize triplet excitons. Phosphorescent materials have higher luminescence efficiency than fluorescent materials because phosphorescent materials can utilize 75% triplet excitons and 25% singlet excitons, while fluorescent materials only utilize 25% singlet excitons. Phosphorescent materials are usually organic metal compounds containing heavy metals, and the luminescent layer formed by them is composed of a host material and a dopant material, and the dopant material emits light by transferring energy from the host material.
[0006] At present, organic metal complexes and organic electroluminescent devices with phosphorescent emission have been reported, and patents have also disclosed a variety of organic metal complex phosphorescent materials, but their brightness, purity and luminous efficiency still cannot meet current needs. Therefore, it is necessary to develop novel materials with better properties, especially to develop blue or green phosphorescent materials with high efficiency and high reliability. Summary of the invention
[0007] The purpose of the present invention is to provide a new organic electrophosphorescent material, which is applied to an organic electroluminescent device. The prepared electroluminescent device exhibits superior performances of high purity, high brightness and high efficiency.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides an organic electrophosphorescent material, comprising a metal atom M and a first ligand coordinated with the metal atom M, wherein the relative atomic mass of the metal atom M is greater than 40, and the structure of the first ligand is as shown in Formula A:
[0010]
[0011] in:
[0012] R1 to R3, when they appear each time, are identical or different, indicating mono-substitution, poly-substitution or no substitution; R1 to R3 are independently selected from hydrogen atoms, deuterium atoms, halogen atoms, substituted or unsubstituted C1 to C 20 Alkyl, substituted or unsubstituted C3~C 20 Cycloalkyl, substituted or unsubstituted C1~C 20 Heteroalkyl, substituted or unsubstituted C1~C 20 deuterated alkyl, cyano, substituted or unsubstituted C1~C 20 Alkoxy, substituted or unsubstituted C1~C 20 Alkylamino, substituted or unsubstituted C1~C 20 Alkylthio, substituted or unsubstituted C6~C 30 aromatic group, substituted or unsubstituted C3~C 30Heterocyclic aromatic groups and combinations thereof, and / or any two or more of R1 to R3 are bridged to form a ring structure;
[0013] The group W=W represents
[0014] Z1-Z8 represent CR4 or N the same or differently each time they appear;
[0015] X and Y are independently selected from O, S and NR5;
[0016] R4 to R5 are each independently a hydrogen atom, a deuterium atom, a halogen atom, a substituted or unsubstituted C1 to C 20 Alkyl, substituted or unsubstituted C3~C 20 Cycloalkyl, substituted or unsubstituted C1~C 20 Heteroalkyl, substituted or unsubstituted C1~C 20 deuterated alkyl, cyano, substituted or unsubstituted C1~C 20 Alkoxy, substituted or unsubstituted C1~C 20 Alkylamino, substituted or unsubstituted C1~C 20 Alkylthio, substituted or unsubstituted C6~C 30 aromatic group, substituted or unsubstituted C3~C 30 Heterocyclic aromatic groups and combinations thereof;
[0017] The dotted line represents the binding site between the first ligand shown in formula A and the metal atom M.
[0018] According to some embodiments of the present invention, the luminescent material further comprises a second ligand L coordinated with the metal M, wherein L is a monovalent dicoordinate anion.
[0019] Preferably, the metal M is Ir.
[0020] According to some embodiments of the present invention, the luminescent material has a structure as shown in Formula I:
[0021]
[0022] Wherein, L is a monovalent dicoordinate anion;
[0023] The definitions of R1-R3, X, Z1-Z4 and group W=W are the same as those in formula A, and n is 1, 2 or 3.
[0024] According to some embodiments of the present invention, the general formula I can be represented by the following structure:
[0025]
[0026] Wherein, the definitions of R1-R3, X, Y, Z1-Z8, L and n are the same as those in Formula I.
[0027] According to some embodiments of the present invention, L is a monovalent bidentate anionic ligand.
[0028] According to a preferred embodiment of the present invention, L is any one of phenylpyridyl, substituted phenylpyridyl, acetylacetonyl or substituted acetylacetonyl.
[0029] According to a preferred embodiment of the present invention, L is a group represented by formula La or formula Lb:
[0030]
[0031] In some embodiments, in Formula La, R 12 ~R 19 are independently selected from hydrogen atoms, deuterium atoms, substituted or unsubstituted C1 to C 20 Alkyl, substituted or unsubstituted C1~C 20 deuterated alkyl, substituted or unsubstituted C1~C 20 Alkoxy, substituted or unsubstituted C1~C 20 Alkylamino, substituted or unsubstituted C1~C 20 alkylthio, fluorine atom, substituted or unsubstituted C6~C 30 aromatic group, substituted or unsubstituted C3~C 30 Heterocyclic aromatic groups and combinations thereof.
[0032] In some embodiments, in Formula La, R 12 ~R 19 Any two or more of them are connected by bridges to form a ring structure.
[0033] In some embodiments, in Formula Lb, R 20 ~R 26 are independently selected from hydrogen atoms, deuterium atoms, substituted or unsubstituted C1 to C 20 Alkyl, substituted or unsubstituted C1~C 20 deuterated alkyl, substituted or unsubstituted C1~C 20 Alkoxy, substituted or unsubstituted C1~C 20 Alkylamino, substituted or unsubstituted C1~C 20 alkylthio, fluorine atom, substituted or unsubstituted C6~C 30 aromatic group, substituted or unsubstituted C3~C 30 Heterocyclic aromatic groups and combinations thereof.
[0034] In some embodiments, in Formula Lb, R 20 ~R26 Any two or more of them are connected by bridges to form a ring structure.
[0035] According to a preferred embodiment of the present invention, the luminescent material is a compound represented by Formula IV, Formula V or Formula VI:
[0036]
[0037] wherein m is 1 or 2; R1 to R3, the group W=W, X, and Z1 to Z4 are defined as in Formula I; R 12 ~R 19 The definition is the same as that of La, R 20 ~R 26 The definition of is the same as that of Lb.
[0038] According to a preferred embodiment of the present invention, in the above formula A, general formula I or general formula IV or general formula V or general formula VI, R1 to R3 are independently selected from hydrogen atoms, deuterium atoms, C1 to C5 alkyl groups, C1 to C5 deuterated alkyl groups, C3 to C6 cycloalkyl groups, cyano groups, alkoxy groups containing 1 to 5 C atoms, alkylamino groups containing 1 to 5 C atoms, alkylthio groups containing 1 to 5 C atoms, fluorine atoms, trifluoromethyl groups, phenyl groups, substituted phenyl groups and C3 to C 20 Heterocyclic aromatic group.
[0039] According to some embodiments of the present invention, any two or more of the R1 to R3 are bridged to form a ring structure. In some embodiments, the ring structure is any one of a substituted or unsubstituted five-membered ring, a substituted or unsubstituted six-membered ring, a substituted or unsubstituted five-membered heterocycle, and a substituted or unsubstituted six-membered heterocycle. Preferably, the substituents used in the substitution are selected from C1 to C5 alkyl, phenyl, and benzo. In some preferred embodiments, the ring structure is selected from benzo ring, furan ring, thien ring, and cyclopentene ring.
[0040] In the present invention, the five-membered heterocyclic ring or the six-membered heterocyclic ring contains at least one heteroatom, and the heteroatom is arbitrarily selected from oxygen atom, sulfur atom and nitrogen atom.
[0041] In the present invention, the C1-C5 alkyl group may be a straight-chain alkyl group or a branched alkyl group, such as methyl, ethyl, n-propane, isopropyl, sec-butyl, n-butyl, isobutyl, tert-butyl, pentyl, neopentyl, etc.
[0042] In the present invention, the C1-C5 deuterated alkyl group is a C1-C5 alkyl group in which part of the hydrogen atoms are replaced by deuterium, wherein the C1-C5 alkyl group may be a straight-chain alkyl group or a branched alkyl group.
[0043] According to some embodiments of the present invention, the C1-C5 deuterated alkyl group is selected from deuterated methyl, deuterated isopropyl, deuterated pentyl and deuterated neopentyl.
[0044] In the present invention, the alkoxy group containing 1 to 5 C atoms is C n H 2n+1 The group represented by O-, wherein n is an integer between 1 and 5.
[0045] According to some embodiments of the present invention, the C1-C5 alkoxy group is selected from methoxy and ethoxy.
[0046] According to a preferred embodiment of the present invention, in the general formula V, R 12 ~R 19 are independently selected from hydrogen atoms, deuterium atoms, C1-C5 alkyl groups, C3-C6 cycloalkyl groups, fluorine atoms, phenyl groups, substituted phenyl groups, C1-C5 deuterated alkyl groups, cyano groups, alkoxy groups containing 1 to 5 C atoms, alkylamino groups containing 1 to 5 C atoms, alkylthio groups containing 1 to 5 C atoms, trifluoromethyl groups, and C3-C 20 Heterocyclic aromatic group.
[0047] According to some embodiments of the present invention, in Formula V, R 12 ~R 19 Any two or more of them are bridged to form a parallel ring structure. In some embodiments, the parallel ring structure is any one of a substituted or unsubstituted five-membered ring, a substituted or unsubstituted six-membered ring, a substituted or unsubstituted five-membered heterocycle, and a substituted or unsubstituted six-membered heterocycle; preferably, the substituent used is selected from C1-C5 alkyl, phenyl, benzo, pyrido, alkyl-substituted pyrido, and deuterated alkyl-substituted pyrido.
[0048] According to a preferred embodiment of the present invention, in the general formula VI, the R 20 ~R 26 They are independently selected from a hydrogen atom, a deuterium atom, a C1-C5 alkyl group, a C3-C6 cycloalkyl group, a fluorine atom, a C1-C5 deuterated alkyl group, an alkoxy group containing 1 to 5 C atoms, an alkylamino group containing 1 to 5 C atoms, an alkylthio group containing 1 to 5 C atoms and a trifluoromethyl group.
[0049] According to a preferred embodiment of the present invention, in the above formula A, general formula I or general formula IV or general formula V or general formula VI, R1 to R3 are independently and arbitrarily selected from a hydrogen atom, a C1 to C5 alkyl group, a C1 to C5 deuterated alkyl group, a phenyl group, a fluorine atom, an alkoxy group containing 1 to 5 C atoms and a trifluoromethyl group.
[0050] According to a more preferred embodiment of the present invention, in the above formula A, general formula I or general formula IV or general formula V or general formula VI, R1 to R3 are independently and arbitrarily selected from hydrogen atom, methyl, deuterated methyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, deuterated isopropyl, phenyl, pentyl, deuterated pentyl, fluorine atom and methoxy group.
[0051] According to some embodiments of the present invention, in the above formula A, general formula I or general formula IV or general formula V or general formula VI, any two or more of R1 to R3 are bridged to form a ring structure. In some embodiments, the ring structure is any one of a substituted or unsubstituted five-membered ring, a substituted or unsubstituted six-membered ring, and a substituted or unsubstituted five-membered heterocyclic ring. Preferably, the substituents used in the substitution are selected from C1 to C5 alkyl, phenyl and benzo. In some preferred embodiments, the ring structure is any one of a substituted or unsubstituted benzene ring, a substituted or unsubstituted furan ring, a substituted or unsubstituted thiophene ring, and a substituted or unsubstituted cyclopentene ring. More preferably, the substituents used in the substitution are benzo or methyl. In some embodiments, the five-membered heterocyclic ring has at least one heteroatom, and the heteroatom is arbitrarily selected from oxygen atoms and sulfur atoms.
[0052] According to a preferred embodiment of the present invention, in the general formula V, R 12 ~R 19 Each is independently selected from a hydrogen atom, a C1-C5 alkyl group, a fluorine atom, a phenyl group and a C1-C5 deuterated alkyl group.
[0053] According to a more preferred embodiment of the present invention, in the general formula V, R 12 ~R 19 They are each independently selected from a hydrogen atom, a methyl group, a fluorine atom, a phenyl group, a deuterated methyl group, an isopropyl group and a deuterated isopropyl group.
[0054] According to some embodiments of the present invention, in Formula V, R 12 ~R 19 Any two or more of them are connected by bridges to form a ring structure. In some embodiments, the ring structure is any one of a substituted or unsubstituted six-membered ring, a substituted or unsubstituted five-membered heterocyclic ring, and the substituents used in the substitution are selected from C1-C5 alkyl, phenyl, benzo, pyrido, pyrido substituted by an alkyl containing 1 to 5 C atoms, and pyrido substituted by a deuterated alkyl containing 1 to 5 C atoms. In some preferred embodiments, the ring structure is any one of a substituted or unsubstituted benzene ring, a substituted or unsubstituted furan ring, and preferably, the substituents used in the substitution are pyrido substituted by a deuterated methyl, pyrido substituted by a methyl, or a benzo. In some embodiments, the five-membered heterocyclic ring has at least one heteroatom, and the heteroatom is arbitrarily selected from an oxygen atom and a sulfur atom.
[0055] According to a preferred embodiment of the present invention, in the above general formula VI, R 20 ~R 26 They are independently selected from a hydrogen atom, a deuterium atom and a C1-C5 alkyl group.
[0056] More preferably, in the general formula VI, R 20 ~R 26 are each independently selected from a hydrogen atom, a methyl group and an ethyl group.
[0057] According to some embodiments of the present invention, in the above formula A, general formula I or general formula IV or general formula V or general formula VI, R4 to R5 are independently selected from hydrogen atoms, deuterium atoms, fluorine atoms, C1 to C5 alkyl groups, C1 to C5 deuterated alkyl groups, cyano groups, alkoxy groups containing 1 to 5 C atoms, alkylamino groups containing 1 to 5 C atoms, alkylthio groups containing 1 to 5 C atoms, trifluoromethyl groups, phenyl groups, substituted phenyl groups and C3 to C 20 Heterocyclic aromatic group.
[0058] According to a preferred embodiment of the present invention, in the above-mentioned general formula I or general formula IV or general formula V or general formula VI, R4~R5 are independently selected from hydrogen atom, methyl, deuterated methyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, deuterated isopropyl, phenyl, pentyl, deuterated pentyl, fluorine atom and methoxy group.
[0059] According to a more preferred embodiment of the present invention, in the formula A, formula I, formula IV to formula VI, the group W=W is selected from the following structures:
[0060]
[0061] According to a preferred embodiment of the present invention, L is selected from the following groups:
[0062]
[0063]
[0064] According to a preferred embodiment of the present invention, the luminescent material is selected from the compounds shown in the following structures:
[0065]
[0066]
[0067]
[0068]
[0069]
[0070]
[0071] In a second aspect, the present invention provides the use of the organic electrophosphorescent material in the preparation of an organic electroluminescent device.
[0072] Preferably, the organic electrophosphorescent material is used as a dye material of the main material of the light-emitting layer in an organic electroluminescent device. The luminescent material of the present invention is used as a dye doped in an organic electroluminescent device to emit light, and the electroluminescent device prepared using the phosphorescent material of the present invention exhibits superior performance of high purity, high brightness and high efficiency.
[0073] Further preferably, the doping concentration of the phosphorescent material in the host material is 2-10%, preferably 3-8%, and more preferably 4-6%. When the doping concentration of the phosphorescent material in the host material is about 5%, the performance of the device is optimal. The doping concentration is a mass percentage concentration.
[0074] In a third aspect, the present invention provides an organic electroluminescent device, comprising a light-emitting layer, wherein the light-emitting layer comprises the phosphorescent material provided by the present invention.
[0075] Preferably, the light-emitting layer comprises a host material and a dye material, and the dye material comprises the phosphorescent material provided by the present invention.
[0076] More preferably, the doping concentration of the phosphorescent material in the host material is 2-10%, preferably 3-8%, more preferably 4-6%, and further preferably 4.5-5.5%.
[0077] Specifically, the organic electroluminescent device includes a substrate, and an anode layer, a plurality of light-emitting unit layers and a cathode layer sequentially formed on the substrate; the light-emitting unit layer includes a hole injection layer, a hole transport layer, a light-emitting layer, and an electron transport layer, the hole injection layer is formed on the anode layer, the hole transport layer is formed on the hole injection layer, the cathode layer is formed on the electron transport layer, and there are multiple light-emitting layers between the hole transport layer and the electron transport layer. The light-emitting material of the light-emitting layer contains the iridium-containing phosphorescent light-emitting material provided by the present invention.
[0078] In a fourth aspect, the present invention provides a display device, comprising the organic electroluminescent device described in the third aspect.
[0079] In a fifth aspect, the present invention provides a lighting device, comprising the organic electroluminescent device described in the third aspect.
[0080] Compared with the prior art, the present invention has the following advantages:
[0081] 1. The present invention provides a new type of organic electrophosphorescent material, which can be used as red and green phosphorescent material;
[0082] 2. Compared with the currently commonly used phosphorescent materials, the organic electroluminescent device prepared by using the phosphorescent luminescent material of the present invention exhibits superior performance of high purity, high brightness and high efficiency, and can effectively solve the problems of currently commonly used phosphorescent materials in terms of low color purity, low luminous efficiency and short life;
[0083] 3. The luminescent material obtained by the combination of different ligands in the present invention can not only adjust the luminescent color, but also improve the photoelectric performance of the organic electroluminescent device, and can meet people's different needs for the device from different angles. DETAILED DESCRIPTION
[0084] The technical scheme of the present invention is described in detail below through specific examples. The following examples are used to illustrate the present invention, but are not used to limit the scope of the present invention. Any other equivalent changes or modifications completed without departing from the spirit disclosed by the present invention should be included in the scope of the claims.
[0085] Synthesis of ligand P
[0086] The synthetic route is as follows:
[0087]
[0088] The synthesis process is as follows:
[0089] (1) Under nitrogen protection, with tetrakistriphenylphosphine palladium as catalyst, toluene as solvent, and cesium carbonate as alkaline conditions, 1-bromo-2-nitrobenzene and aniline reacted at 100°C for 18 hours to obtain intermediate P-01.
[0090] (2) Under nitrogen protection, using ethanol as solvent, the reaction was carried out at 80°C for 24 hours, and anhydrous stannous chloride was used to reduce P-01 to obtain intermediate P-02.
[0091] (3) Under nitrogen protection, P-02 and 2-fluorobenzoyl chloride were reacted in a system of N,N-diisopropylethylamine, DMAP and tetrahydrofuran at room temperature for 18 hours to obtain the intermediate P-03.
[0092] (4) Under nitrogen protection, P-03 was refluxed in glacial acetic acid at 140 °C for 18 h to obtain the intermediate P-04.
[0093] (5) Under nitrogen protection, with cesium carbonate as base and dimethylacetamide as solvent, P-04 and raw material M were reacted at 150°C for 16 hours to obtain intermediate P-05.
[0094] (6) Under nitrogen protection, with palladium acetate and X-phos as catalysts and DBU as a base, P-05 was refluxed in a toluene system for 24 hours to obtain the ligand compound P.
[0095] Example 1: Synthesis of ligand P1
[0096]
[0097] The synthetic route is as follows:
[0098]
[0099] The specific experimental steps are:
[0100] (1) In a 2L dry round-bottom flask equipped with a mechanical stirrer, 1-bromo-2-nitrobenzene (100g, 1.0eq, 495.03mmol), aniline (50.71g, 1.1eq, 544.54mmol), cesium carbonate (403.23g, 2.5eq, 1.24mol), tetrakistriphenylphosphine palladium (11.44g, 0.02eq, 9.9mmol) and 1L of toluene were added in sequence under a nitrogen atmosphere and reacted at 100°C for 18 hours. After the reaction, an appropriate amount of water was added, extracted with ethyl acetate, the organic phase was separated, dried over anhydrous magnesium sulfate, concentrated, and separated by column chromatography to obtain a red solid intermediate P1-01 (97.6g, yield 92%).
[0101] (2) In a 2L dry round-bottom flask equipped with a mechanical stirrer, P1-01 (97g, 1.0eq, 452.8mmol), anhydrous stannous chloride (429.27g, 5.0eq, 2.26mol) and 1L of ethanol were added in sequence under a nitrogen atmosphere, and the mixture was refluxed at 80°C for 24 hours. The reaction solution changed from red turbidity to colorless clarity. After the reaction was completed, the solvent was removed under reduced pressure, an appropriate amount of ethyl acetate was added, and a sodium hydroxide solution was added dropwise to adjust the pH to 8-9. The precipitated solid was filtered and washed with an appropriate amount of ethyl acetate. The organic phase was combined and separated, dried over anhydrous magnesium sulfate, concentrated, and separated by column chromatography to obtain a white solid intermediate P1-02 (75g, yield 90%).
[0102] (3) In a 2L dry round-bottom flask equipped with a mechanical stirrer, P1-02 (75g, 1.0eq, 407.07mmol), N,N-diisopropylethylamine (131.5g, 2.5eq, 1.02mol), DMAP (1.49g, 0.03eq, 12.21mmol) and 1L of tetrahydrofuran were added in sequence under a nitrogen atmosphere, and 2-fluorobenzoyl chloride (71g, 1.1eq, 447.78mmol) was added dropwise at 0°C, and the reaction was continued at room temperature for 18 hours. After the reaction, an appropriate amount of water was added, extracted with ethyl acetate, the organic phase was separated, dried over anhydrous magnesium sulfate, concentrated, and separated by column chromatography to obtain a beige solid intermediate P1-03 (118.5g, yield 95%).
[0103] (4) In a 2L dry round-bottom flask equipped with a mechanical stirrer, P1-03 (118.5 g, 1.0 eq, 306.34 mmol) and 500 mL of glacial acetic acid were added in sequence under a nitrogen atmosphere, and the mixture was reacted at 140°C for 18 hours. After the reaction, most of the glacial acetic acid was removed under reduced pressure, and an appropriate amount of sodium carbonate solution was added to adjust the pH to neutral. The mixture was extracted with ethyl acetate, and the organic phase was separated, dried over anhydrous magnesium sulfate, concentrated, and separated by column chromatography to obtain a pink-purple solid intermediate P1-04 (109 g, yield 98%).
[0104] (5) In a 2L dry round-bottom flask equipped with a mechanical stirrer, P1-04 (28.8 g, 0.1 mol), raw material M-1: 3-bromodibenzo[b,d]furan-2-ol (26.2 g, 0.1 mol), cesium carbonate (97.8 g, 0.3 mol) and 500 mL of dimethylacetamide were added in sequence under a nitrogen atmosphere, and reacted at 150°C for 16 hours. After the reaction was completed, the temperature was cooled to room temperature, and a large amount of white solid was washed out with water, filtered, dissolved in dichloromethane, dried over anhydrous magnesium sulfate, filtered, the solvent was dried, and separated by column chromatography to obtain an off-white solid intermediate P1-05 (46.6 g, yield 88%).
[0105] (6) In a 2L dry round-bottom flask equipped with a mechanical stirrer, P1-05 (53 g, 0.1 mol), palladium acetate (1.1 g, 0.005 mol), X-phos (4.8 g, 0.01 mol), DBU (30.4 g, 0.2 mol), and 500 mL of toluene were added in sequence under a nitrogen atmosphere, and the mixture was heated under reflux for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered with diatomaceous earth, and the diatomaceous earth was washed with an appropriate amount of dichloromethane. The filtrate was combined, the solvent was dried, and white solid P1 (32.4 g, yield 72%) was obtained by column chromatography.
[0106] Product MS (m / e): 450; Elemental analysis (C 31 H 18N2O2): Theoretical value C: 82.65%, H: 4.03%, N: 6.22%; Measured value C: 82.44%, H: 4.09%, N: 6.31%.
[0107] According to the ligand synthesis method in Example 1, the raw material M-1 is replaced with raw materials M-2 to M-8, and other ligand compounds (P2 to P8) can be synthesized respectively. The specific structures are shown in Table 1.
[0108] Table 1
[0109]
[0110]
[0111] Example 2: Synthesis of Compound I-1
[0112]
[0113] The reaction formula is as follows:
[0114]
[0115] The specific experimental steps are as follows: In a 250ml three-necked flask equipped with a magnetic stirrer and a reflux condenser, add Ir(acac)3 (4.9g, 10mmol), ligand P1 (18g, 40mmol), and 150mL of glycerol in sequence. Evacuate and fill with N2 for 5 times to remove oxygen from the system. Heat and reflux in an oil bath at 190°C under N2 protection for 24 hours. Cool naturally to room temperature, filter, wash with water, n-hexane, and ether in sequence, and dry to obtain a yellow crude product. Dissolve in CH2Cl2 and separate on a column, eluent CH2Cl2, drain the solvent, and obtain 4.5 grams of yellow powder with a yield of 36%.
[0116] Product MS (m / e): 1540; Elemental analysis (C 93 H 51 IrN6O6): Theoretical value C: 72.50%, H: 3.34%, N: 5.45%; Measured value C: 72.35%, H: 3.39%, N: 5.40%.
[0117] Example 3: Synthesis of Compound I-44
[0118]
[0119] The reaction formula is as follows:
[0120]
[0121] The specific experimental steps are:
[0122] (1) In a 100 mL three-necked flask equipped with a mechanical stirrer, a reflux condenser and a nitrogen protection device, add 2-(4-(trifluoromethyl)phenyl)pyridine (3.3 g, 15 mmol), hydrated iridium trichloride (2.01 g, 6 mmol), 45 mL of ethylene glycol monoethyl ether and 15 mL of distilled water in sequence. Evacuate and fill with N2 for five times to remove oxygen from the system. Heat to 110°C and reflux for 24 hours. After natural cooling, add 10 mL of distilled water, shake, filter, wash with water and ethanol. Vacuum dry to obtain 3.1 g of yellow solid dichloro bridged intermediate crude product I-44-1 with a yield of 78%.
[0123] (2) In a 500 mL three-necked flask equipped with a nitrogen protection device, the dichloro bridged intermediate I-44-1 (13.4 g, 10 mmol) and 150 ml of dichloromethane were added in sequence, and stirred thoroughly. Then, a 200 ml methanol solution of silver trifluoromethanesulfonate (6.4 g, 25 mmol) was added, and stirred for 24 hours under light-proof conditions. After cooling to room temperature, the generated AgCl was filtered out with diatomaceous earth, and the filtrate was dried to obtain a yellowish brown solid powder. This solid was used directly in the next step without treatment.
[0124] (3) In a 250 ml three-necked flask, add the khaki solid (6.0 g, 7 mmol) obtained in step (2) above and ligand P2 (9.5 g, 21 mmol), then add 100 ml of ethanol, heat the mixture under reflux for 36 hours, cool the reactants to room temperature, filter the generated yellow solid, dissolve the solid in dichloromethane, and separate by column chromatography to obtain 6.1 g of bright yellow solid (yield 80%).
[0125] Product MS (m / e): 1086; Elemental analysis (C 55 H 31 F6IrN4O2): Theoretical value C: 60.82%, H: 2.88%, N: 5.16%; Measured value C: 60.69%, H: 2.92%, N: 5.21%.
[0126] Example 4: Synthesis of Compound I-45
[0127]
[0128] Referring to the synthesis steps of Example 3, 5-(trifluoromethyl)-2-(4-(trifluoromethyl)phenyl)pyridine was used instead of 2-(4-(trifluoromethyl)phenyl)pyridine, ligand P3 was used instead of P2, and other raw materials and steps were the same as Example 3 to obtain compound I-45.
[0129] Product MS (m / e): 1254; Elemental analysis (C 57 H 29 F 12IrN4S2): Theoretical value C: 54.59%, H: 2.33%, N: 4.47%; Measured value C: 54.44%, H: 2.38%, N: 4.42%.
[0130] Example 5: Synthesis of Compound I-76
[0131]
[0132] The reaction formula is as follows:
[0133]
[0134] The specific experimental steps are:
[0135] (1) In a 500 mL three-necked flask equipped with a mechanical stirrer, a reflux condenser and a nitrogen protection device, add in sequence: ligand P8 (13.1 g, 25 mmol), hydrated iridium trichloride (3.35 g, 10 mmol), 90 mL of ethylene glycol monoethyl ether, and 30 mL of distilled water. Vacuum and fill with N2 for 5 times to remove oxygen from the system. Heat to 110°C and reflux for 24 hours. After natural cooling, add 10 mL of distilled water, shake, filter, wash with water, and wash with ethanol. Vacuum dry to obtain 11.3 g of crude dichlorobridged intermediate I-76-1 as a yellow solid with a yield of about 74%.
[0136] (2) In a 250 ml three-necked flask equipped with a magnetic stirrer and a reflux condenser, add the above intermediate I-76-1 (7.5 g, 5 mmol), 5-(methyl-d3)-2-phenylpyridine (4.3 g, 25 mmol), anhydrous Na2CO3 (2.35 g, 22 mmol) and 100 mL of ethylene glycol monoethyl ether in sequence. Evacuate and fill with N2 for 5 times to remove oxygen from the system. Heat and reflux in an oil bath at 120°C under N2 protection for 24 hours. Cool naturally to room temperature, filter, wash with water, n-hexane, and ether in sequence, and dry to obtain a yellow crude product. Dissolve in CH2Cl2 and separate on a column, eluent CH2Cl2, and drain the solvent to obtain 11.3 g of yellow powder I-76, with a yield of 80%.
[0137] Product MS (m / e): 1412; Elemental analysis (C 86 H 51 D3IrN7O2): Theoretical value C: 73.12%, H: 4.07%, N: 6.94%; Measured value C: 73.00%, H: 4.12%, N: 6.88%.
[0138] Example 6: Synthesis of Compound I-80
[0139]
[0140] Referring to the synthesis steps of Example 5, 5-(methyl-d3)-2-(phenyl-2,3,4,5-d4)pyridine is used instead of 5-(methyl-d3)-2-phenylpyridine, ligand P4 is used instead of P8, and other raw materials and steps are the same as Example 5 to obtain compound I-76.
[0141] Product MS (m / e): 1330; Elemental analysis (C 74 H 37 D7IrN5S4): Theoretical value C: 66.79%, H: 3.86%, N: 5.26%; Measured value C: 66.63%, H: 3.82%, N: 5.38%.
[0142] Example 7: Synthesis of Compound I-97
[0143]
[0144] Referring to the synthesis steps of Example 5, 2,2,6,6-tetramethylheptane-3,5-dione was used instead of 5-(methyl-d3)-2-phenylpyridine, ligand P5 was used instead of P8, and other raw materials and steps were the same as Example 5 to obtain compound I-97.
[0145] Product MS (m / e): 1306; Elemental analysis (C 73 H 53 IrN4O4S2): Theoretical value C: 67.11%, H: 4.09%, N: 4.29%; Measured value C: 67.01%, H: 4.06%, N: 4.35%.
[0146] Example 8: Synthesis of Compound I-100
[0147]
[0148] Referring to the synthesis steps of Example 5, 3,7-diethylnonane-4,6-dione was used instead of 5-(methyl-d3)-2-phenylpyridine, ligand P7 was used instead of P8, and other raw materials and steps were the same as Example 5 to obtain compound I-100.
[0149] Product MS (m / e): 1484; Elemental analysis (C 87 H 67 IrN6O2S2): Theoretical value C: 70.37%, H: 4.55%, N: 5.66%; Measured value C: 70.23%, H: 4.59%, N: 5.74%.
[0150] Example 9: Synthesis of Compound I-103
[0151]
[0152] Referring to the synthesis steps of Example 5, 3,7-diethylnonane-4,6-dione was used instead of 5-(methyl-d3)-2-phenylpyridine, ligand P6 was used instead of P8, and other raw materials and steps were the same as Example 5 to obtain compound I-103.
[0153] Product MS (m / e): 1334; Elemental analysis (C 75 H 57 IrN4O4S2): Theoretical value C: 67.50%, H: 4.30%, N: 4.20%; Measured value C: 67.38%, H: 4.34%, N: 4.27%.
[0154] Referring to the above synthesis method, other specific phosphorescent compounds listed in the present invention were synthesized.
[0155] Example 10: Stability Verification Experiment
[0156] 5 g of the commercial compound GD01 and the compound I-1 prepared in the present invention were respectively placed in a high vacuum sublimation apparatus and heated at 6.0*10 -4 The sublimation was carried out at a vacuum degree of 1.3 Pascal and a temperature of 295°C for 20 hours. The sublimation results are shown in Table 2.
[0157] Control Compound
[0158] Table 2
[0159]
[0160] From the data in the above table, it can be seen that the purity of the compound I-1 provided by the present invention remains unchanged after sublimation, while the purity of the compound GD01 decreases significantly after sublimation. It can be seen that the phosphorescent material of the present invention has good thermal stability.
[0161] Example 11: Preparation of OLED Device
[0162] The application examples of the OLED device of the compound of the present invention are as follows. This embodiment provides a group of OLED devices, the structure of which is: ITO / HATCN (6nm) / HT01:TAPC (2%, 50nm) / CBP:3% of the phosphorescent light-emitting material compound of the present invention (25nm) / ET01:QLi (1:1) (35nm) / LiF (1nm) / Al (120nm).
[0163] The molecular structure of each functional layer material is as follows:
[0164]
[0165] Preparation of OLED-1 device:
[0166] The compound I-1 prepared in the present invention is selected as a phosphorescent material with a doping concentration of 3% to prepare an OLED device. The specific preparation method is as follows:
[0167] (1) a glass plate coated with an ITO transparent conductive layer was ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, ultrasonically degreased in a mixed solvent of acetone:ethanol (volume ratio 1:1), baked in a clean environment until the water was completely removed, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam;
[0168] (2) Place the glass substrate with the anode in a vacuum chamber and evacuate the chamber to a vacuum of 1×10 -5 ~9×10 -3 Pa, vacuum evaporating HATCN as a hole injection layer on the above anode layer film, the evaporation rate is 0.1nm / s, and the total evaporation film thickness is 6nm; then evaporating HT01:TAPC with a mass ratio of 98:2 as the hole transport layer of the device, the evaporation rate is 0.1nm / s, and the evaporation film thickness is 50nm;
[0169] (3) vacuum evaporating EML on the hole transport layer as the light-emitting layer of the device, the EML comprising the main material CBP and the dye material I-1 of the present invention, with a doping mass percentage concentration of 3%, forming an organic light-emitting layer of the device, the evaporation rate is 0.2 nm / s, and the total evaporation film thickness is 25 nm;
[0170] (4) ET01:QLi with a mass ratio of 1:1 was evaporated on the light-emitting layer as the electron transport material of the device electron transport layer, the evaporation rate was 0.1 nm / s, and the total evaporation film thickness was 35 nm;
[0171] (5) Vacuum evaporation of 1 nm thick LiF as the electron injection layer and 120 nm thick Al as the cathode of the device were performed on the electron transport layer. After packaging, the OLED-1 device was obtained.
[0172] Preparation of OLED-2 to OLED-3 devices:
[0173] According to the above-mentioned method for preparing the OLED-1 device, only the doping concentration of the dye material I-1 of the present invention in the main material CBP in step (3) was changed from 3% to 5% and 8%, respectively, to prepare OLED-2 and OLED-3 devices.
[0174] The performance of the devices OLED-1 to OLED-3 prepared above was tested. The performance test results of each device are shown in Table 3. The peak wavelength, voltage and current efficiency in Table 3 are obtained when the current density is 20 mA / cm 2The lifetime is measured as the time required for the initial luminous brightness of 20,000 nit to decay to 95% of the initial brightness.
[0175] Table 3
[0176]
[0177] Comparing the test results of the above three light-emitting devices, it can be seen that when the doping concentration is adjusted from 3% to 5%, the voltage, current efficiency and lifespan are improved. When the concentration continues to increase to 8%, phosphorescence quenching occurs, the voltage increases, and the current efficiency and lifespan decrease. The device performance OLED-2 is the best, that is, when the doping concentration is about 5%, the brightness is the highest and the efficiency is also the highest.
[0178] Preparation of OLED-4 to OLED-10 devices:
[0179] According to the above-mentioned method for preparing the OLED-1 device, the dye material I-1 of the present invention in step (3) is replaced by compounds I-44, I-45, I-76, I-80, I-97, I-100, and I-103, respectively, and the doping concentration in the main material CBP is 5%, and OLED-4 to OLED-10 devices are prepared.
[0180] Comparative device 1 is prepared by using commercial compound GD01 as a dye material to replace dye material I-1 in OLED-1 device, and the doping concentration in host material CBP is 5%.
[0181] The performance of the device OLED-2, device OLED-4 to device OLED-10, and comparative device 1 prepared above were tested. The performance test results of each device are shown in Table 4. The peak wavelength, voltage, and current efficiency in Table 4 are obtained at a current density of 20 mA / cm 2 The lifetime is measured as the time required for the initial luminous brightness of 20,000 nit to decay to 95% of the initial brightness.
[0182] Table 4
[0183]
[0184]
[0185] As can be seen from Table 4, compared with GD01, the device voltage prepared by the compound of the present invention is lower, and due to the improved stability of compound I-1 itself, the corresponding device luminous efficiency is improved, and the life span is significantly extended. Among them, compounds I-44, I-45, I-76, and I-80 use ligand P and phenylpyridine compounds to coordinate with metal iridium, and the device shows pure green, the voltage is reduced by 10% to 12%, the current efficiency is increased by 8% to 10%, and the life span is extended by 16% to 19%, especially with deuterated phenylpyridine compounds. The best effect is achieved. Compounds I-97, I-100, and I-103 use ligand P and diketone compounds to coordinate with metal iridium, and the device shows red shift, the voltage is reduced by 7% to 8%, the current efficiency is increased by 6% to 7%, and the life span is extended by 13% to 14%. Compound I-1 uses pure ligand P to coordinate with iridium, and the voltage, current efficiency and life span are also improved.
[0186] The compounds of the present invention with different coordination modes can adjust the color of the light emission, and also have a significant impact on the photoelectric performance and device life of the corresponding device, showing the wide adjustability of the light emission performance and device data of the compounds of the present invention, and can provide solutions for different customer needs. Therefore, the phosphorescent luminescent material provided by the present invention can effectively solve the problems of the currently commonly used phosphorescent materials in terms of color purity, luminous efficiency and life, and the organic electroluminescent device prepared by using the phosphorescent luminescent material of the present invention shows the superior performance of high purity, high efficiency and long life, and the comprehensive performance of the device is significantly improved.
[0187] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. An organic electrophosphorescent material having a structure shown in any one of Formula IV to Formula VI: in, R1 to R3, when they appear each time, are the same or different, indicating mono-substitution, poly-substitution or no substitution; R1 to R3 are each independently selected from a hydrogen atom, a deuterium atom, a C1 to C5 alkyl group, and a C1 to C5 deuterated alkyl group; The group W=W is selected from the following structures: Z1-Z4 are each independently selected from CR4; X is selected from O or S; R4 is selected from a hydrogen atom, a deuterium atom, a C1-C5 chain alkyl group and a C1-C5 deuterated alkyl group; R 12 ~R 19 Each is independently selected from a hydrogen atom, a deuterium atom, a C1-C5 alkyl group, a fluorine atom, a trifluoromethyl group, a phenyl group and a C1-C5 deuterated alkyl group; R 20 ~R 26 Each is independently selected from a hydrogen atom, a deuterium atom, a C1-C5 alkyl group and a C1-C5 deuterated alkyl group; m is 1 or 2.
2. The luminescent material according to claim 1, characterized in that In Formula IV to Formula VI, R1 to R3 are each independently selected from a hydrogen atom, a C1 to C5 alkyl group, and a C1 to C5 deuterated alkyl group.
3. The luminescent material according to claim 2, characterized in that In Formula IV to Formula VI, R1 to R3 are each independently selected from a hydrogen atom, a methyl group, a deuterated methyl group, a n-propyl group, an isopropyl group, a n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a deuterated isopropyl group, a pentyl group and a deuterated pentyl group.
4. The luminescent material according to claim 1, characterized in that In formula V, R 12 ~R 19 Each is independently selected from a hydrogen atom, a deuterium atom, a methyl group, a fluorine atom, a trifluoromethyl group, a phenyl group, a deuterated methyl group, an isopropyl group and a deuterated isopropyl group.
5. The luminescent material according to claim 1, characterized in that In Formula VI, R 20 ~R 26 Each is independently selected from a hydrogen atom, a deuterium atom and a C1-C5 alkyl group.
6. The luminescent material according to claim 5, characterized in that In Formula VI, R 20 ~R 26 Each is independently selected from a hydrogen atom, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a sec-butyl group, an n-butyl group, an isobutyl group, a tert-butyl group, a pentyl group and a neopentyl group.
7. The luminescent material according to claim 1, characterized in that In Formula IV to Formula VI, R4 is selected from a hydrogen atom, a methyl group, a deuterated methyl group, a n-propyl group, an isopropyl group, a n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a deuterated isopropyl group, a pentyl group and a deuterated pentyl group.
8. The luminescent material according to claim 1, characterized in that Selected from the following groups:
9. The luminescent material according to claim 1, characterized in that Selected from the following groups:
10. The luminescent material according to claim 1, characterized in that R1~R3 are all hydrogen atoms; Z1-Z4 are each independently selected from C and CH; X is selected from O and S; The group W=W is selected from the following structures: R 12 ~R 19 are each independently selected from a hydrogen atom, a deuterium atom, a trifluoromethyl group and a deuterated methyl group; R 20 ~R 26 are each independently selected from a hydrogen atom, a methyl group and an ethyl group.
11. An organic electrophosphorescent material, characterized in that: The luminescent material has a structure shown in the following formula:
12. Use of the luminescent material according to any one of claims 1 to 11 in an organic electroluminescent device.
13. The use according to claim 12, characterized in that: The light-emitting material is used as a dye material of a host material of a light-emitting layer in an organic electroluminescent device.
14. The use according to claim 13, characterized in that The doping mass percentage of the luminescent material in the host material is 2-10%.
15. The use according to claim 13, characterized in that: The doping mass percentage of the luminescent material in the host material is 3-8%.
16. The use according to claim 13, characterized in that: The doping mass percentage of the luminescent material in the host material is 4-6%. 17 . An organic electroluminescent device comprising a light-emitting layer, wherein a dye material of a host material of the light-emitting layer contains the light-emitting material according to claim 1 .
18. The organic electroluminescent device according to claim 17, characterized in that: The organic electroluminescent device comprises, from bottom to top, a substrate, an anode layer, a light-emitting unit layer including a light-emitting layer, and a cathode layer.
19. The organic electroluminescent device according to claim 18, characterized in that: The light-emitting unit layer further includes one or more of a hole injection layer, a hole transport layer, and an electron transport layer.
20. The organic electroluminescent device according to claim 17, characterized in that: The doping mass percentage of the luminescent material in the host material is 2-12%.
21. The organic electroluminescent device according to claim 17, characterized in that: The doping mass percentage of the luminescent material in the host material is 3-8%.
22. The organic electroluminescent device according to claim 17, characterized in that: The doping mass percentage of the luminescent material in the host material is 4-6%.
23. A display device or lighting device, characterized in that: An organic electroluminescent device comprising any one of claims 17 to 22.
Citation Information
Patent Citations
Compound, organic light-emitting device and display device
CN108218867A
Iridium complex containing benzimidazole structure and application thereof
CN112321647A